Cost analysis of planned out-of-hospital births in Italy - Cicero, Roberta Vittoria; Colaceci, Sofia; Amata, Rosanna; Spandonaro, Federico (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: In Italy, the main birthplace is a hospital, and only a few women choose an out-of-hospital setting. This study assessed the costs related to delivery in different birthplaces in Italy. Methods: The cost analysis considered direct and amortizable costs associated with mother-child care in physiological conditions. An analysis of the hospital births considered the Diagnoses-Related Groups 373 and 391. To estimate the cost of the births assisted privately by freelance midwives, an evaluation based on an experts’ opinion was carried out. Results: Childbirth hospital care in Italy amounts to € 1832.00, and birth in an out-of-hospital setting accredited with the National Health System has a full cost of € 1345.19 in the ‘maternity home’ and € 909.60 at home. The average cost of the birth in ‘private maternity homes’ amounted to € 3260.00, while at-home births amounted to € 2910.00. Conclusions: Any accreditation of out-of-hospital settings by the NHS would considerably reduce the waste of economic resources compared to hospital childbirth.